Proceedings of the 7th Annual International Conference on Mobile Computing and Networking 2001
DOI: 10.1145/381677.381684
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Ad Hoc wireless networks

Abstract: Early simulation experience with wireless ad hoc networks suggests that their capacity can be surprisingly low, due to the requirement that nodes forward each others' packets. The achievable capacity depends on network size, traffic patterns, and detailed local radio interactions. This paper examines these factors alone and in combination, using simulation and analysis from first principles. Our results include both specific constants and general scaling relationships helpful in understanding the limitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,229 publications
(165 citation statements)
references
References 10 publications
(12 reference statements)
3
146
0
5
Order By: Relevance
“…Their simulations always include the use of RTS/CTS, and the TCP flows, which compete to access the network ressource, may only go through the network on a segment of the chain (whereas in the case of a substitution networks, it is very likely that the traffic is exchanged from one endpoint to the other). During the same year, the authors of [7] study the capacity of multihop wireless networks based on IEEE 802.11 DCF and, specifically, the capacity of multihop chains. The performance are studied using the simulator Ns2.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Their simulations always include the use of RTS/CTS, and the TCP flows, which compete to access the network ressource, may only go through the network on a segment of the chain (whereas in the case of a substitution networks, it is very likely that the traffic is exchanged from one endpoint to the other). During the same year, the authors of [7] study the capacity of multihop wireless networks based on IEEE 802.11 DCF and, specifically, the capacity of multihop chains. The performance are studied using the simulator Ns2.…”
Section: State-of-the-artmentioning
confidence: 99%
“…In [2], the performance of various routing algorithms for wireless ad-hoc networks were compared in a simulation environment built around ns-2 based on a static range model [7]. In [16], the authors examined the throughput capacities of 802.11b wireless adhoc networks [11], through theoretical studies and ns-2 simulations. They found that the 802.11 MAC protocol yields throughput that is markedly less than is possible with an optimal schedule, either because it failed to detect an idle link immediately, or it generates too much local collision.…”
Section: B Comparison With Cellular Analysismentioning
confidence: 99%
“…IEEE 802.11 BROADCAST SCALABILITY With vehicular densities that can vary from very sparse to more than 150 cars/lane/km, a very important property of the VANET MAC layer ought to be scalability. The classic unicast IEEE 802.11 has long been known to have problems in this area, with the throughput achievable by a station drastically dropping in crowded environments [4].…”
Section: Introductionmentioning
confidence: 99%